A century of oil and gas exploration in Albania: Assessment of Naturally Occurring Radioactive Materials (NORMs). (November 2015) - Xhixha, G.; Baldoncini, M.; Callegari, I.; Colonna, T.; Hasani, F.; Mantovani, F.; Shala, F.; Strati, V.; Xhixha Kaçeli, M.
Abstract: The Naturally Occurring Radioactive Materials (NORMs) that are potentially generated from oil and gas extractions in Albania have been disposed of without regulations for many decades, and therefore, an extensive survey in one of the most productive regions (Vlora-Elbasan) was performed. A total of 52 gamma ray spectrometry measurements of soil, oil-sand, sludge, produced water and crude oil samples were performed. We discovered that relatively low activity concentrations of 226 Ra, 228 Ra, 228 Th and 40 K, with concentrations of 23 ± 2 Bq/kg, 23 ± 2 Bq/kg, 24 ± 3 Bq/kg and 549 ± 12 Bq/kg, respectively, came from the oil-sands produced by the hydrocarbon extraction of the molasses formations. The mineralogical characterizations and the 228 Ra/ 40 K and 226 Ra/ 40 K ratios of these Neogene deposits confirmed the predictions of the geological and geodynamic models of a dismantling of the Mesozoic source rocks. The average activity concentrations (±standard deviations) of the radium isotopes ( 226 Ra and 228 Ra) and of the 228 Th and 40 K radionuclides in soil samples were 20 ± 5 Bq/kg, 25 ± 10 Bq/kg, 25 ± 9 Bq/kg and 326 ± 83 Bq/kg, respectively. Based on the measurements in this study, the future radiological assessments of other fields in the region should be strategically planned to focus on the oil-sands from the molasses sediments. Disequilibrium in the 228 Ra decay segment was not observed in the soil, sludge or oil-sand samples within the standard uncertainties. After a detailed radiological characterization of the four primary oil fields, we concluded that the outdoor absorbed dose rate never exceeded the worldwide population weighted average absorbed dose rate in outdoor air from terrestrial gamma radiation.